2006
DOI: 10.1111/j.1360-0443.2006.01321.x
|View full text |Cite
|
Sign up to set email alerts
|

Methadone versus buprenorphine in pregnant addicts: a double‐blind, double‐dummy comparison study

Abstract: This preliminary study had limited power to detect differences but the trends observed suggest this kind of research is practicable and that further studies are warranted.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

17
218
2
7

Year Published

2008
2008
2020
2020

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 209 publications
(244 citation statements)
references
References 27 publications
17
218
2
7
Order By: Relevance
“…The difference in treatment effect between BUP and MET was not significant from two RCTs 19, 20 and three OBSs 38, 39, 41 (Table 2 and Fig. 2a), but the direction differed by study design.…”
Section: Resultsmentioning
confidence: 89%
See 4 more Smart Citations
“…The difference in treatment effect between BUP and MET was not significant from two RCTs 19, 20 and three OBSs 38, 39, 41 (Table 2 and Fig. 2a), but the direction differed by study design.…”
Section: Resultsmentioning
confidence: 89%
“…The effect estimate from three RCTs 19, 20, 21 indicated lower risk of preterm birth for BUP compared with MET. Similarly, the treatment effect among seven medium ROB OBSs 18, 38, 39, 41, 42, 43, 48 showed that BUP was associated with a decreased risk of preterm birth compared with MET (Table 2 and Fig.…”
Section: Resultsmentioning
confidence: 94%
See 3 more Smart Citations